Pneumothorax in the cases of silicosis in southern part of Rajasthan - Sharma, Rishi K.; Luhadia, Atul; Luhadia, Shanti K.; Mathur, Yash; Pandya, Harshil; Methe, Prithviraj (International Journal of Advances in Medicine, 2017)
Background: Silicosis is an occupational lung disease caused by inhalation of dust containing crystalline silica particles of size 0.5-5 microns in diameter. It commonly occurs in workers involved in quarrying, mining, sandblasting, tunneling, foundry work and ceramics. Pneumothorax is one of the complications of silicosis. The occurrence of pneumothorax in a patient with silicosis is a rare event, but it may be fatal. The incidence of secondary spontaneous pneumothorax (SSP) in silicosis as such is not known. This study aims to report the cases of secondary spontaneous pneumothorax in patients of silicosis in Southern part of Rajasthan. Methods: 50 patients of silicosis established by historical, clinical evaluation and radiological evidence with increased dyspnoea were included in the study. In all patients Chest X ray was done immediately. Results: Among 50 patients of silicosis with increased dyspnoea, Chest X ray showed pneumothorax in 20 patients of which 4 had bilateral pneumothorax, 7 had right pneumothorax and 9 had left pneumothorax. The mean duration of exposure to silica particles was 10 years (5 to 15 years). All the patients had various degrees of dyspnoea and chest pain. Tube thoracostomy was performed in 15 patients while 5 patients were managed conservatively with oxygen and bronchodilators. Conclusions: Our study showed an increased incidence of secondary pneumothorax in silicosis patients. The occurrence of pneumothorax, though rare in silicosis is a potentially life-threatening complication and may cause serious morbidity and mortality. The patients of silicosis who develop sudden onset of dyspnoea should be promptly investigated for this complication.